Jurnal Skripsi Analisis Teknik Permainan Gitar pada Komposisi "MOONTAN" karya Andrew York - Junaidi, Roby; Herdiati, Dian (Jurnal Penelitian Musik, 2024)
The purpose of this research is to know The Guitar playing technique used in the song Moontan by Andrew York. The research object focused on guitar palying Technique in the song Moontan by Andrew YorkThis research method using descriptive qualitative method. Data obtained by way of observation, documentation, interview, and literature study. The results of this study are the Moontan song which has a tuning called Scordatura. The techniques used in the Moontan song are categorized in 4 Important factor when playing guitar classic according to Shearer, namely Speed, Strength, Color Tone and Economic Movement. The game techniques that can be categorized in the speed of the moontan song are the techniques of Tirando, rasgueado, barre, hammer on, pull off, hammer on with the right and pull off with the left hand. Techniques that require power, use a Hammer with the Right Hand, Hammer with the Left Hand, Pull with the left hand, Slap, and Harmonic. The game techniques that require Color Tones used are the Tirando, Apoyando, and Rasgueado techniques. Techniques that require the Economic Movement on the Moontan song ask for Arpeggio, Barre and Damp String.